2010
DOI: 10.1097/jto.0b013e3181c814e7
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Cisplatin and Vinorelbine for Completely Resected Non-small Cell Lung Cancer: Subgroup Analysis of the Lung Adjuvant Cisplatin Evaluation

Abstract: In subgroup analyses, adjuvant cisplatin-vinorelbine provides a superior survival benefit and can be recommended in completely resected stages II and III non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
151
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(159 citation statements)
references
References 22 publications
5
151
1
2
Order By: Relevance
“…That analysis used data from four clinical trials, collectively involving 1,888 patients. In fact, those results are more consistent than are the results of other metaanalyses compared in the same study, (15) which allowed the use of other chemotherapy regimens (HR = 0.95; 95% CI: 0.86-1.05; interaction test = 0.04). The median survival described in the present study, as well as that described in the Arriagada et al study, (8) is clearly lower than the median survival of 94 months described in the study conducted by Winton et al (12) However, caution is required when comparing these results, because differences in patient selection are likely to have influenced this evaluation.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…That analysis used data from four clinical trials, collectively involving 1,888 patients. In fact, those results are more consistent than are the results of other metaanalyses compared in the same study, (15) which allowed the use of other chemotherapy regimens (HR = 0.95; 95% CI: 0.86-1.05; interaction test = 0.04). The median survival described in the present study, as well as that described in the Arriagada et al study, (8) is clearly lower than the median survival of 94 months described in the study conducted by Winton et al (12) However, caution is required when comparing these results, because differences in patient selection are likely to have influenced this evaluation.…”
contrasting
confidence: 54%
“…In another study, (14) this improvement was 11% after more than nine years of follow-up, which is in disagreement with the findings of the Arriagada et al study. (11) In addition, in a recent meta-analysis, (15) extremely positive results were obtained with the cisplatinvinorelbine combination, with a reduction in the overall mortality rate of 8.9% in comparison with observation (hazard ratio [HR] = 0.80; 95% CI: 0.70-0.91; p < 0.001). That analysis used data from four clinical trials, collectively involving 1,888 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin (CDDP)-based chemotherapies are recommended as the adjuvant chemotherapy in surgically resected stage II and IIIA NSCLC (4,5). Among the CDDP-based combination chemotherapies, chemotherapy with CDDP and vinorelbine haveproven to be beneficial for survival in NSCLC (6). Kato et al (7) and Hamada et al (8) demonstrated that tegafur-uracil (UFT) adjuvant therapy improved the overall survival period in stage I lung adenocarcinoma, however, this result has not yet been proven worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ANITA (Adjuvant Navelbine International Trialist Association) and JBR-10 (National Cancer Institute of Canada Clinical Trial Group) trials also confirm the survival benefit of adjuvant cisplatinvinorelbine chemotherapy in patients with NSCLC at I-IIIA even after follow-up for 9.3 years (Winton et al, 2005;Douillard et al, 2006;Butts et al, 2010). In addition, the LACE (Lung Adjuvant Cisplatin Evaluation) collaborative group and ISA (Italian Survey on adjuvant treatment trial) independently confirm that the effect of NP treatment was significantly better than that of platinumbased combination Douillard et al, 2010;Banna et al, 2011). Interestingly, chemotherapy with uracil-tegafur, an alternative of cisplatin-based adjuvant therapy, also improves the survival rate in Japanese patients with NSCLC (Imaizumi et al, 2005;Nakagawa et al, 2006).…”
Section: Introductionmentioning
confidence: 67%